2014
DOI: 10.1007/978-981-287-128-2_19
|View full text |Cite
|
Sign up to set email alerts
|

Fiber Optic Sensors: Short Review and Applications

Abstract: An extensive review of optical fiber sensors and the most beneficial applications is presented in this chapter. Although electrical sensing technologies have been successfully deployed in countless applications, the introduction of optical sensing, engineers and scientists can now perform measurements that were previously impractical or, in some cases, impossible with conventional electrical sensors. At present, many real-world applications already use both approaches to combine both benefits. The inherent adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 13 publications
(8 reference statements)
0
31
0
Order By: Relevance
“…A study using TOF revealed the successful detection of dengue virus (DENV) at 1 pM within 15 min [15]. However, this sensor requires precise alignment, high cleanliness and maintenance, and very careful handling, since the fibers can break easily [16,17]. To address these downsides, researchers are exploring the SPR sensor which has a low cost, is simple to use and environment-friendly, and provides high accuracy and fast measurements [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…A study using TOF revealed the successful detection of dengue virus (DENV) at 1 pM within 15 min [15]. However, this sensor requires precise alignment, high cleanliness and maintenance, and very careful handling, since the fibers can break easily [16,17]. To address these downsides, researchers are exploring the SPR sensor which has a low cost, is simple to use and environment-friendly, and provides high accuracy and fast measurements [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Such unique capabilities make fiber optics the preferred sensing platform in a myriad of fields, including oil and gas industry [3], structural health monitoring [4], healthcare sector [5], among others [6], [7]. Generally, FOSs can be classified based on the measurand's spatial distribution to include point, integrated, quasi-distributed, and distributed sensors [8]. The majority of such FOSs are based on single-mode fiber (SMF), which can be standard SMF, photonic-crystal fiber (PCF) [9], or polarization-maintaining fiber (PMF) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Optical sensors and fiber optic sensors have some inherent advantages compared with their electrical counterparts: they can provide high selectivity, immunity to electromagnetic interference (EMI), a wide dynamic range, easy multiplexing and the possibility to be deployed in hostile environments thanks to their electrical and chemical inertness [1,2]. By measuring intensity, phase and/or refractive index changes, optical sensors can sense a wide variety of parameters, including temperature, pressure, vibration, and presence of specific chemical species [1,3].…”
Section: Introductionmentioning
confidence: 99%